Phosphorus adsorption in Ceará State soils, Brazil. - Moreira, Fátima (2008)
Samples (0-20 cm) from four different soils of the Ceará State, Brazil (Cambissolo, Argissolo, Neossolo, Latossolo), were studied with the objectives of determining the effects of the physical, chemical and mineralogical attributes on the soil phosphorus adsorption capacity. Sand fraction samples were determined separately. The soil samples were mixed with a CaCl2 0.01M, with addition to 0; 1; 2; 3.5; 5; 8; 12 and 15 mg P.kg-1 soil as KH2PO4 and maintained in contact for 24 hours. The phosphorus was analyzed from the supernatant in order to determine the amount of P adsorbed by the soils. The same procedure was used for sand fraction samples, except for changes on phosphorus concentrations: 0; 0.2; 0.4; 0.8; 1.6 e 3.2 mg P.kg-1 soil, to verify a possible phosphorus adsorption capacity of sand fraction. The maximum P adsorption capacity (MPAC) was determined for all soil and fractions through the linear model of the Langmuir equation. The MPAC values ranged from 109.89 to 344.83 mg P.Kg-1 soil. The highest MPAC value was for the Haplic Cambisol soil. The results showed that the soil attributes closest correlated with the soil MPAC were soil organic matter content and the soil cation exchangeable capacity. Significant correlations were, also, found between the MPAC and the soil contents of amorphous iron oxides, crystalline iron oxides and total iron. It was found out that iron adsorption in the sand fraction can be attributed to presence of organic matter on samples as well as iron oxides.